Expression of p27 and p53: comparative analysis of uterine carcinosarcoma and endometrial carcinoma. Issue 2 (1st February 2004) - Abargel, A.; Avinoach, I.; Kravtsov, V.; Boaz, M.; Glezerman, M.; Menczer, J.
Abstract : The aim of the study was to assess both p27 and p53 expression in the stromal and epithelial component of carcinosarcoma and to assess if their expression in the latter is different than in endometrial carcinoma. Immunohistochemical staining for p27 and p53 was performed on paraffin-embedded tissue blocks of 18 uterine specimens with carcinosarcoma and their expression assessed. Their expression in the epithelial element was also compared to that in 35 paraffin-embedded tissue blocks of endometrial endometrioid carcinoma. Reduced p27 expression was observed in a similarly high proportion of the stromal (77.8%) as well as of the epithelial component (66.7%) of carcinosarcoma. Although statistically not significant, the proportion of reduced p27 expression in endometrial carcinoma (85.7%) was higher than in the epithelial element of carcinosarcoma. The percentage of p53 overexpression in both elements of carcinosarcomas and in endometrial carcinomas was low and also similar (27.8 and 20.0%, respectively). Our results indicate that reduced p27 expression is common and p53 overexpression is infrequent in carcinosarcoma. Their similar rates of expression in the stromal and epithelial elements of the tumor support the contention of a monoclonal origin of carcinosarcoma. Unexpectedly, reduced p27 expression is more common in endometrial carcinoma than in the epithelial element of carcinosarcoma, in spite of the less favorable prognosticators and outcome in the latter. Further studies of p27 expression in carcinosarcoma are indicated to establish its clinical value in this aggressive malignancy.